Evaluation of Nonuniformity of Elastic Properties of Sheets Made from Closed-Сell Polyolefin Foams by Acoustic Method - O. P. Bogdan; D. V. Zlobin; O. V. Murav'eva; S. M. Molin; A. V. Platunov (Приборы и методы измерений)
The widespread use of polyolefin foams in strategically important industries is due to their high thermal, sound and vibration insulation properties. The aim of the work was to evaluate the non-uniformity of elastic properties over the area of sheets of polyolefin foams of various types using the acoustic non-contact shadow amplitude method of testing and confirmation by the structural analysis method.The article presents the developed installation and a new method of non-contact acoustic testing of sheets made of closed-cell polyolefin foams based on recording the amplitude of the pulse that passed through the sheet and allowing to assess to the unevenness of its elastic properties during scanning. Studies of uneven elastic properties were carried out on sheets of closed-cell polyolefin foams of the ISOLON 500 and ISOLON 300 brands which differ in material and manufacturing technology (technique of cross-linking, method and multiplicity of foaming).It is shown that the absolute amplitude of the signal and its spread relative to the average value is affected by the structure of the foam polyolefin material and its heterogeneity over the area of the studied sheet determined by the production technology which is confirmed visually using microscopy.Studies have shown the effect on the indications unevenness of the method of obtaining and the apparent density of the material. It is shown that the most uneven elastic properties and structure belong to sheets of polyolefin foam obtained by chemical cross-linking technology (the unevenness of Δ was 6.5 %). Among the physically cross-linked sheets of polyolefin foam the most uniform in structure and elastic properties are samples made of ethylene vinyl acetate with Δ = 3.8 %, as well as sheets with a high foaming rate (Δ = 3.9 %). The unevenness of structure of the studied sheets of polyolefin foams was confirmed by optical microscopy of sections in two mutually perpendicular directions.